The Effect of Smart Indonesia Program (PIP) on the Risk of School Dropout: A Propensity Score Matching Analysis Based on National Data - Haryono; Rumayya (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — This study provides new empirical evidence on the effectiveness of the Smart Indonesia Program (Program Indonesia Pintar, or PIP), a cash transfer program specifically targeting education, in reducing the risk of school dropout among low-income students during the second year of the COVID-19 pandemic. Unlike previous studies, it focuses on the differential impact across education levels using nationally representative post-pandemic data. Research Objectives — The research aims to evaluate the impact of PIP on reducing school dropout rates among students aged 6-21 years from low-income households in Indonesia. It also seeks to identify at which educational level the program has the most pronounced effect. Research Methods — This study employed the propensity score matching (PSM) method using the March 2022 National Socioeconomic Survey (SUSENAS) data. The approach controls for selection bias in estimating the causal impact of PIP on educational outcomes. Empirical Results — The findings showed that PIP significantly reduced the risk of dropout across all education levels. The most substantial impacts were observed at the junior and senior high school levels, where PIP recipients showed a lower risk of dropout than non-recipients by 2.11 and 2.04 percentage points, respectively. At the elementary level, the risk of dropout decreased by 0.34 percentage points. Implications — These results underscore the importance of expanding PIP coverage and establishing a robust monitoring system for fund utilization to enhance the program's effectiveness in promoting educational participation among poor households.